2018
DOI: 10.2147/ott.s156556
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of plasma mammaglobin A expression in breast carcinoma patients: a meta-analysis

Abstract: Mammaglobin A expression in peripheral blood (PB) of breast carcinoma patients has been evaluated by various studies, but the findings have been inconsistent. This meta-analysis aimed to clarify the prognostic value of mammaglobin A in the PB of breast carcinoma patients and define its relationships with clinicopathological features. PubMed, EMBASE, and the Cochrane Library databases were systematically searched for eligible studies through September 26, 2017. A total of 20 studies involving 2,323 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A meta-analysis of several studies revealed that higher levels of circulating mammaglobin-a in plasma correlates with lymph node metastasis and advanced tumor stage. [16][17][18][19] Furthermore, enzyme linked immunosorbent diagnostic assay (ELISA) has been used to show that secreted mammaglobin-a protein is elevated in breast cancer patient blood. 20 Predictive analysis of mammaglobin-a protein structure reveals a putative transmembrane domain suggesting that mammaglobin-a may be anchored at the plasma membrane on breast cells.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of several studies revealed that higher levels of circulating mammaglobin-a in plasma correlates with lymph node metastasis and advanced tumor stage. [16][17][18][19] Furthermore, enzyme linked immunosorbent diagnostic assay (ELISA) has been used to show that secreted mammaglobin-a protein is elevated in breast cancer patient blood. 20 Predictive analysis of mammaglobin-a protein structure reveals a putative transmembrane domain suggesting that mammaglobin-a may be anchored at the plasma membrane on breast cells.…”
Section: Introductionmentioning
confidence: 99%
“…MVD, the major angiogenesis-related parameter [32] does not always correlate with MGB expression hence the difficulty of ensuring a complete estimation of the patients' prognosis. However, Hu et al [33] have demonstrated the implications of MGB-A as an independent prognostic biomarker in breast cancer. Plasma MGB-A is associated with lymph node metastases and advanced tumor stage, but no correlation was found between MGB-A and tumor size, tumor differentiation, menopausal status and hormone status of breast cancer patients [33].…”
Section: Resultsmentioning
confidence: 99%
“…However, Hu et al [33] have demonstrated the implications of MGB-A as an independent prognostic biomarker in breast cancer. Plasma MGB-A is associated with lymph node metastases and advanced tumor stage, but no correlation was found between MGB-A and tumor size, tumor differentiation, menopausal status and hormone status of breast cancer patients [33]. Our results show a variable MGB expression in the molecular types of breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…It has been described that MAG possesses specificity and high immunogenicity and also regulates the tumorigenesis and aggressiveness in BC by increasing the cellular proliferation, migration, and invasion of cancer cells. MAG is responsible for activating signaling pathways such as; MAPK, FAK, MMP, and NF-κB [103], and is involved in the expression of IL-2. In vitro experiments showed that positive cells to the expression of mammaglobin could promote the activation of CD4+ and CD8+ T cells capable of recognizing and lysate cancer cells [104].…”
Section: Mammaglobin-αmentioning
confidence: 99%